PENGUNGKAPAN AKTOR KEJAHATAN MELALUI KOMPASTV LIVE (ANALISIS PEMBERITAAN POLISI TANGKAP PENYERANG NOVEL BASWEDAN) - Suf Kasman (Fakultas Dakwah dan Komunikasi, 2020)
The research was aimed to analyze is KOMPASTV LIVE. Currently, technology has gained increasing attention as a major means to provide his services. representations of crime are partly responsible for this. Certain crimes are often over-reported on TV. With an increasing rate of violent crimes across the country as well as an uptick in crime in the news.Two people attacked the senior investigator in April 2017 by throwing acid on his face, causing serious injuries to his eyes. At the time of the attack, Novel Baswedan was leading KPK investigations in several major cases. After two-and-a-half-years of investigation, the National Police arrested two active police officers, identified only as RM and RB, as suspects in the attack.